How Does an Education-based Buddhist Morality Serve as a Foundation to Enhance the Spiritual Intelligence of Teenage Students? - Agus Nalanda Wijanata; Sidartha Adi Gautama; Komang Sutawan; Widiyanto Widiyanto; Eko Pramono; Widi Astuti; Susanto Susanto (International Journal of Science and Applied Science: Conference Series, 2024)
Buddhism or the Buddhist Morality or Pancasila refers to the application of the five moral principles in Buddhism, namely: not killing, not stealing, not lying, not having inappropriate sexual relations, and not using alcohol. These principles are the ethical foundation for living a good and harmonious life. Through Pancasila Buddhist divination, a person hones their spiritual intelligence by living a life that is moral, mindful, and in harmony with universal values. Spiritual Intelligence is the ability to understand the meaning of life, make ethical decisions, and foster empathy and self-awareness. This research is included in the survey/interview method with a descriptive quantitative approach. Descriptive quantitative research is research whose task is to analyze data in the form of numbers used to find out and describe existing phenomena to find a relationship or influence between 2 variables to obtain conclusions from the research results. Quantitative research is a research method based on the philosophy of positivism because it fulfills scientific principles, namely concrete/empirical, objective, measurable, rational, and systematic.